2014
DOI: 10.1038/ni.2828
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific control of early B cell development by the transcription factor Ikaros

Abstract: Ikaros is an essential regulator of lymphopoiesis. Here, we studied the B-cell-specific function of Ikaros by conditional Ikzf1 inactivation in pro-B cells. B-cell development was arrested at an aberrant 'pro-B' cell stage characterized by increased cell adhesion and loss of pre-B cell receptor signaling. Ikaros was found to activate genes coding for pre-BCR signal transducers and to repress genes involved in the downregulation of pre-BCR signaling and upregulation of the integrin signaling pathway. Unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
204
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(226 citation statements)
references
References 66 publications
(117 reference statements)
14
204
1
4
Order By: Relevance
“…However, enrichment of Ikaros-binding events in the vicinity of genes that are misregulated in Ikzf1 mutant cells was not observed despite evidence that Ikaros regulates stage-specific genes during two stages of B-cell development, similar to our findings in thymocytes. Instead, the study by Schwickert et al (2014), like our studies and those of others (Zhang et al 2011;Schjerven et al 2013), reported preferential binding in the vicinity of a large percentage of transcriptionally active genes or in the vicinity of control regions that exhibit histone modifications characteristic of transcriptionally active chromatin. These findings raise the possibility that the Ikaros-binding events observed by ChIP-seq may reflect a broader role in genome organization rather than a specific role in regulating genes in the vicinity of the binding sites.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…However, enrichment of Ikaros-binding events in the vicinity of genes that are misregulated in Ikzf1 mutant cells was not observed despite evidence that Ikaros regulates stage-specific genes during two stages of B-cell development, similar to our findings in thymocytes. Instead, the study by Schwickert et al (2014), like our studies and those of others (Zhang et al 2011;Schjerven et al 2013), reported preferential binding in the vicinity of a large percentage of transcriptionally active genes or in the vicinity of control regions that exhibit histone modifications characteristic of transcriptionally active chromatin. These findings raise the possibility that the Ikaros-binding events observed by ChIP-seq may reflect a broader role in genome organization rather than a specific role in regulating genes in the vicinity of the binding sites.…”
Section: Discussionsupporting
confidence: 44%
“…Schwickert et al (2014) showed that the genomic sites occupied by Ikaros differ at different stages of B-cell development. However, enrichment of Ikaros-binding events in the vicinity of genes that are misregulated in Ikzf1 mutant cells was not observed despite evidence that Ikaros regulates stage-specific genes during two stages of B-cell development, similar to our findings in thymocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NuRD complex is unique, especially in lymphocytes, as it can modulate access to nucleosomes through Mi-2β, restrict chromatin through histone deacetylases (HDAC1-2), and, with the addition of IKAROS proteins, target chromatin in a sequence-and lineage-specific manner (Kim et al 1999;Zhang et al 2011). Indeed, in Tcell and B-cell precursors, Mi-2β is highly enriched at IKAROS-binding sites in the vicinity of transcriptionally active lymphoid genes Schwickert et al 2014). The presence of the NuRD complex at these active regulatory sites may serve as a harbinger for their shutdown at a later differentiation stage (Whyte et al 2012;Yamada et al 2014).…”
Section: Post-translational Modificationsmentioning
confidence: 99%